Strategi Perusahaan Maskapai Penerbangan dalam Menghadapi Pandemi Covid-19: Pendekatan Akuntansi Manajemen - Natanael, Johanes Abraham; Irawan, Ferry (PT WIM Solusi Prima, 2024)
The Covid-19 pandemic has caused many companies to experience a decline in revenue and profits, including airline companies. PT Garuda Indonesia is one of the companies included in the tourism industry ecosystem which has also been affected by the Covid-19 pandemic. This research aims to investigate the strategies companies choose to face the Covid-19 pandemic. This research uses a qualitative method with a case study approach. The research results show that cost efficiency and product differentiation strategies are able to increase company revenues.